Psychology of Language Acquisition and EFL Teaching Methodology: A Critical Overview - Omar, Abdul-Majeed (Gezira Journal of Educational Sciences and Humanities, 2018)
This paper aims at scrutinizing the psychological background of language acquisition theories with particular reference to English as a second/ foreign language teaching methodology. It is hoped that this would provide foreign language teachers with  key issues in psychology  that will help them to understand better the ways in which their students learn and to provide a source of knowledge that may help them to improve their classroom practice. The descriptive analytical method will be adopted to conduct this investigation. Two conflicting schools of thought in psychology; namely, the behaviorists' and the mentalists' school, have been discussed and their views about   language learning have been presented .The behaviorists assume that people learn language both native and second, as they learn everything else. Language, according to this approach, is "a set of habits" which can be taught by providing the appropriate stimuli and response until an automatic response to a certain stimulus is attained. The mentalists reject this explanation of language learning as too native asserting that much of the capacity for language learning in humans is "innate" and that language   learning entails insight, thinking and reasoning using complex deductive and inductive procedures. These conflicting schools of psychology have generated a sizeable number of language teaching methods. Eight of these methods have been thoroughly discussed, compared, and their merits and demerits highlighted. It is clearly demonstrated that none of these methods is perfect or without drawbacks, and that none of them could be used successfully if applied in its pure form. Hence, the researcher suggests an eclectic approach to EFL teaching .However, in order to use this eclectic approach successfully, a teacher must have a detailed knowledge of all methods. This will help him/her to select the most appropriate elements to present his/her lessons.   The study has also hint that the use of modern technology has boosted foreign language teaching and made its learning less cumbersome and more interesting.